БОШЛАНҒИЧ ТАЪЛИМ ПЕДАГОГЛАРИНИ ПЕДАГОГИК ЖАРАЁНДА РУҲИЙ ЁНДАШУВ МАСАЛАЛАРИ (Scientific journal of the Fergana State University, 2023)
In this article the problems of psychological education, the psychological impact of emotional communication activities of the child developing are considered.